Experimental investigation of a novel micro-channel flat loop heat pipe (MC-FLHP) for data center cooling and heat recovery. Issue 12 (26th September 2022) - Xiang, Jinwei; Luo, Liang; Wang, Xupeng; Shittu, Samson; Wang, Zhangyuan; Zhao, Xudong; Weng, Chuangbin
ABSTRACT: In this paper, a novel micro-channel flat loop heat pipe (MC-FLHP) for data center cooling and heat recovery is proposed, which has the following novelties and distinguished advantages, i.e., a tightly attached flat heat pipes array with IT server thus reaching a 'server level' cooling for data center, several pre-set micro-grooves which increases the convective heat transfer coefficient, and a separated evaporator-condenser which greatly improves the flexibility of the system's installation. The proposed system with R134a (filling ratio of 30%) as the working fluid is designed, constructed and tested, and the testing results are used to evaluate its thermal recovery efficiency and its impact factors, i.e., simulated heat load, cooling water inlet temperature and height difference between the evaporator and condenser. Under the range of test conditions (e.g., simulated heat load from 500 W to 3000 W, cooling water inlet temperature from 15°C to 24°C, height difference from 0.6 m to 1.0 m), the overall thermal recovery efficiency is in the range 57.34% to 84.52%. It is found that under the specific operational conditions with the simulated heat load of 500 W, cooling water inlet temperature of 15°C, and height difference between the evaporator and the condenser of 0.8 m, a peak thermal recovery efficiency of 84.52% is achieved. This study can help achieve the global goals of green and sustainable data center, and also save data center energy consumption and thus operational costs.